Social Comparison and Self-Presentation Among Adolescent Users of Instagram in The City Of Makassar. - Fakhri, Nurfitriany; Rachim, Ruckmana Ainun; Irdianti, Irdianti (Seminar Nasional LP2M UNM, 2023)
Abstract. The objective of this study is to examine the impact of social comparison on self-presentation within the context of Instagram, a popular social media platform. The participants of this study consisted of adolescents ranging from 12 to 21 years of age, who were actively engaged in the use of Instagram, and residing in Makassar City. The participants in this study consisted of a total of 175 respondents. The sample approach employed in this study utilizes the method of convenience sampling. The findings of this study, which employed a basic regression analysis, indicate a correlation coefficient (r) of 0.419 and a significance level (sig) of 0.00. Additionally, the coefficient of determination (r square) is calculated to be 0.175, suggesting that social comparison contributes to self-presentation by around 17.5%. Consequently, the hypothesis proposed in this study can be deemed acceptable. The findings of this study offer advantages for adolescent Instagram users in understanding the impact of social comparison on self-presentation exhibited on the platform. Additionally, it sheds light on fostering self-assurance and refraining from establishing rigid beauty standards on Instagram. Keywords: Social comparison, Self Presentation, Adolescent, Instagram